Le developpement grinçant dacuite - Salomão, Solange Rios (2007)
Visual acuity is one of the most studied visual functions during the fi rst years of life. Visual acuity reflects the ability to resolve fine details from an observed object. Grating stimuli has been used in infants, pre-verbal and non-verbal patients to evaluate visual acuity. Clinical methods to measure grating acuity currently available along with normal developmental data of this function are presented.